Benefits of the Mediterranean Diet-Wine Association: Role of Components - Silva, Paula; Latruffe, Norbert (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Mediterranean diet is a model of eating based on the traditional foods and drinks of the countries surrounding the Mediterranean Sea. The cultural and the nutritional aspects of the multisecular Mediterranean civilization include diet as a central element of health and wellbeing, including wine, if it is consumed in moderation. In recent decades, it has been promoted worldwide (UNESCO 2010) as one of the healthiest dietary patterns. The objective of this book is to bring the role of wine as part of the Mediterranean diet to light, especially through policy makers, the medical world, and vectors of images.